Bacterial Bridges: Controlling Geometry and Flow Through Bacterial Bridges on Patterned Lubricant‐Infused Surfaces (pLIS) (Small 52/2020). Issue 52 (28th December 2020) - Lei, Wenxi; Krolla, Peter; Schwartz, Thomas; Levkin, Pavel A.
Abstract : In article number 2004575, Thomas Schwartz, Pavel A. Levkin, and co‐workers demonstrate and explain the formation of bacterial bridge structures—micrometer thin strings formed between clusters of Pseudomonas aeruginosa on patterned lubricant infused surfaces (pLIS) during dewetting. This simple method allows to control the geometry, length and alignment of bacterial bridges by using pre‐designed superhydrophobic‐hydrophilic patterns. The method will be important for understanding biofilm formation, structure and function.